WARP decompositions - Hassan Nosratabadi (Rutgers University, Department of Economics, 2017)
The relation between Sen's decomposition of the weak axiom of revealed preferences (WARP), and WARP directional decomposition introduced in Nosratabadi (2017) is investigated. It is argued that the latter generalizes the former. A pairwise transitive WARP decomposition consistent with Sen's property a is given. It is also argued that the notion of referential DM can not be built upon Sen's properties.
Keywords: D11; D81; 330; The Weak Axiom of Revealed Preferences; WARP Decomposition